2019
DOI: 10.1177/2151459319870426
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of High- and Low-Energy Acetabular Fractures in Elderly Patients

Abstract: Introduction: Geriatric patients represent 14% of acetabular fractures and are the fastest growing subset of patients affected by this injury in the US. Treatment outcomes have been reported as inferior to those achieved in younger patients after high-energy (HE) acetabular trauma. This study aimed to compare detailed demographic characteristics and clinical outcomes in elderly patients (≥65 years of age) treated in a tertiary North American trauma center for acetabular fractures after both high- and low-energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…24,25 The results of this case series confirm previous findings indicating that patients in the high-energy fracture group are predominantly male, younger, and have fewer comorbidities than those who sustain low-energy fractures. 8 Higher BMI in our study was associated with surgical intervention, arthritis, and postoperative nerve palsy.…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…24,25 The results of this case series confirm previous findings indicating that patients in the high-energy fracture group are predominantly male, younger, and have fewer comorbidities than those who sustain low-energy fractures. 8 Higher BMI in our study was associated with surgical intervention, arthritis, and postoperative nerve palsy.…”
Section: Discussionmentioning
confidence: 45%
“…A literature search revealed few publications on both highand low-energy geriatric acetabular fracture outcomes. 4,8,[20][21][22] Two of these studies found high-energy fracture patterns to follow similar fracture patterns as the low-energy group, resulting in a majority anterior wall or both column fractures. 8,21 Also, prior studies demonstrate that posterior wall fracture patterns are found to be associated with poorer outcomes.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations